Comparative study of free and liposome-entrapped chloramphenicol against biofilms of potentially pathogenic bacteria isolated from cooling towers - Marcus Vinícius Dias-Souza; Daniel Lucas Soares; Vera Lúcia dos Santos (Elsevier, 2017)
This study aimed to investigate for the first time the in vitro antibiofilm effectiveness of two chloramphenicol liposome formulations against biofilms of potentially pathogenic bacteria associated to corrosion isolated from the water of cooling towers from a Brazilian industry. Antibiofilm assays with liposomes were performed in 96-wells microtiter plates, and data was compared to free chloramphenicol treatment. Chloramphenicol-loaded liposomes were successfully produced using the dehydration-rehydration method, with vesicle diameters of 131 nm (100 nm membrane extrusion) and 182 nm (200 nm membrane extrusion) assessed by dynamic light scattering. The liposomes obtained by 100 nm membrane extrusion were more effective than 200 nm membrane extrusion vesicles against the biofilms after overnight exposure, and the free drug had no antibiofilm effect. Our study open doors for more investigations on liposome entrapment of antimicrobial compounds such as biocides of industrial use, for controlling biofilm formation in aquatic environments.